Administrative and Organizational Cultural Factors Influencing the Performance Effectiveness of Local Administrative Organizations in Lopburi Province: Administrative and Organizational Cultural Factors Influencing the Performance Effectiveness of Local Administrative Organizations in Lopburi Province - Udompan, Angkana (RATANABUTH JOURNAL, 2026)
This research aimed to 1) examine the level of operational effectiveness of local administrative organizations in Lopburi Province, 2) examine the administrative and organizational culture factors influencing the operational effectiveness of local administrative organizations in Lopburi Province, and 3) examine recommendations regarding the operational effectiveness of local administrative organizations in Lopburi Province. The sample consisted of 382 personnel of local administrative organizations in Lopburi Province. The research instrument was a questionnaire. Data were analyzed using mean, standard deviation, and multiple linear regression analysis. The research findings revealed that: 1) the overall operational effectiveness of local administrative organizations in Lopburi Province was at a high level; 2) the administrative factors influencing the operational effectiveness of local administrative organizations in Lopburi Province included leadership, strategic planning and strategic management, and resource management, which collectively predicted 55.50% of the variance (R² = 0.555); 3) the organizational culture factors influencing the operational effectiveness of local administrative organizations in Lopburi Province included achievement-oriented culture and adaptive culture, which collectively predicted 50.70% of the variance (R² = 0.507), with statistical significance at the .01 level; and 4) recommendations for enhancing the operational effectiveness of local administrative organizations in Lopburi Province were as follows: (a) in terms of administration and management, information technology systems should be adopted to enhance efficiency and transparency, and the management skills of professional administrators should be developed; (b) in terms of public service delivery, One-Stop Service systems should be comprehensively implemented across all service areas, and public needs should be systematically surveyed; (c) in terms of human resource management and council affairs, continuous personnel capacity development should be pursued, staff morale should be fostered through fair performance evaluation systems, and transparent council administration systems should be developed; and (d) in terms of financial and fiscal management, personnel should be equipped with enhanced knowledge of financial and fiscal administration, and budget expenditure should be monitored, evaluated, and planned in alignment with public needs.